Indonesian EFL teachers' intercultural profiles in Indonesian universities - Aulia, Muhammad (EduLite: Journal of English Education, Literature and Culture, 2022)
Being a foreign language and an intercultural educator in an English as a Foreign Language (EFL) context is full of complexities. With diverse sociocultural aspects in a context, it would be naïve to implement a set of global profile of culture to all contexts. Therefore, the present study is held to start to investigate complexities on teacher individual level in the implementation of intercultural approach to EFL in Indonesian context. The study strives to interlink between the teacher belief and the characteristics of an intercultural teacher to indicate a teacher personal positioning toward the intercultural pedagogy. Through the method of narrative inquiry and narrative analysis, the teachers’ narratives were collected by interviews and scrutinised. The study revealed that ambivalence and contradiction appeared in the teachers’ beliefs about intercultural pedagogy. It has premises that a teacher’s positioning is affected by learning and teaching experiences, professional development, and personal experiences. Teaching context plays a central role in shaping the practices. The results show capacity building must be advocated and the identical studies must be replicated focusing on how a teacher develops intercultural communicative competence in order to bring quality of intercultural EFL pedagogy in Indonesia.